2004
DOI: 10.1021/ma0492871
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Morphology of Poly(11-undecalactone) Solution-Grown Single Crystals

Abstract: Solution-grown lamellar single crystals of poly(11-undecalactone) (PUDL) have been prepared in 1-hexanol. The lozenge and hexagonal-shaped single crystals were grown simultaneously, and these crystals gave well-resolved electron diffraction diagrams from which the orthogonal reciprocal lattice with the parameters a* ) 1.346 nm -1 , b* ) 2.004 nm -1 , and γ* ) 90°could be determined. The growth faces of both crystals were considered as mainly {110}, and the average chain-folding direction was parallel to these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 46 publications
(129 reference statements)
4
19
0
Order By: Relevance
“…The wide‐angle XRD pattern of a neat PHDL sample, shown in Figure 4, is characterized by two strong reflections at 2 θ equal to 21.40° and 23.79° corresponding to d = 0.415 nm and 0.374 nm indexed by (110) and (200), respectively. This is very similar with the diffraction pattern of PUDL, PDDL, and PPDL, as pointed out by previous papers 29–31. In Table 3 the experimental d ‐spacings and intensities of the main reflections are compared with the refined calculated values.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The wide‐angle XRD pattern of a neat PHDL sample, shown in Figure 4, is characterized by two strong reflections at 2 θ equal to 21.40° and 23.79° corresponding to d = 0.415 nm and 0.374 nm indexed by (110) and (200), respectively. This is very similar with the diffraction pattern of PUDL, PDDL, and PPDL, as pointed out by previous papers 29–31. In Table 3 the experimental d ‐spacings and intensities of the main reflections are compared with the refined calculated values.…”
Section: Resultssupporting
confidence: 87%
“…The refined a and b lattice parameters of PHDL ( m = 15) ( a = 0.746 nm and b = 0.504 nm) are very close to those of polyethylene (PE) ( a = 0.741 nm and b = 0.494 nm),33 PUDL ( m = 10) ( a = 0.743 nm and b = 0.499 nm),29 PDDL ( m = 11) ( a = 0.746 nm and b = 0.500 nm),30 and PPDL ( m = 14) ( a = 0.752 nm and b = 0.502 nm)31 as listed in Table 5, indicating that the lateral cell expansion due to the CO groups does not depend on the number of methylene units in the chain, as previously pointed out by Gazzano et al31 In other words, the effect of the CO group tends to decrease by the large number of methylene units. On the other hand, the c parameters increased with an increase in the number of methylene units in the chain because of the molecular chain having an almost planar zigzag conformation.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Some authors have reported on single crystals of aliphatic polyesters such as poly(ε‐caprolactone) (PCL) . The single crystalline structures of some other biodegradable polyesters including poly(β‐propiolactone), poly(3‐hydroxylbutyrate) (P(3HB)), P(4HB), poly(11‐undecalactone), poly(dvalerolactone), poly(12‐dodecalactone), and poly(15‐pentadecalactone) were also focused. Different types of extracellular polyhydroxybutyrate depolymerases were employed to investigate the degradation of single crystals.…”
Section: Introductionmentioning
confidence: 99%